1998
DOI: 10.1097/00005344-199811000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of a Selective Cyclooxygenase-2 Inhibitor Versus Indomethacin on Renal Blood Flow in Conscious Volume-Depleted Dogs

Abstract: Renal effects of a selective cyclooxygenase-2 (COX-2) inhibitor [MF-Tricyclic; 3-(3,4-difluorophenyl)-4-(4-(methylsulfonyl)phenyl)-2-(5H)-furanone] were studied in control and volume-depleted conscious dogs. MF-Tricyclic was compared with the nonselective COX-1/COX-2 inhibitor indomethacin. Six instrumented male dogs were randomly selected to receive MF-Tricyclic or indomethacin at 10 mg/kg. Volume depletion was effected by a sodium-restricted diet (14 days) with administration of furosemide (7.5 mg/kg, i.v.) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 12 publications
4
28
0
1
Order By: Relevance
“…The ketoprofen group grade was higher than that of the control group, which indicates that fecal occult blood tests may be useful for detection of gastrointestinal bleeding disorders in dogs treated with NSAIDs. Adverse renal effects of NSAIDs result primarily from the decreased synthesis of renal vasodilative PGs (PGE2 and PGI2) [1,3,19,27]. A previous study of ketoprofenassociated adverse renal effects found decreased endogenous creatinine clearance in dogs receiving ketoprofen before castration surgery [8].…”
Section: Discussionmentioning
confidence: 99%
“…The ketoprofen group grade was higher than that of the control group, which indicates that fecal occult blood tests may be useful for detection of gastrointestinal bleeding disorders in dogs treated with NSAIDs. Adverse renal effects of NSAIDs result primarily from the decreased synthesis of renal vasodilative PGs (PGE2 and PGI2) [1,3,19,27]. A previous study of ketoprofenassociated adverse renal effects found decreased endogenous creatinine clearance in dogs receiving ketoprofen before castration surgery [8].…”
Section: Discussionmentioning
confidence: 99%
“…They were sacri®ced at 4 months of age, and number and size of ®bromatoses and gastro-intestinal lesions scored as previously reported . A total of 83 male and 79 female B6-Apc+/Apc1638N mice were assigned to either nodrug, sulindac, DFU, or MF-tricyclic (Chan et al, 1997;Black et al, 1998) to begin after weaning. These drugs were fed to the mice in food pellets at a concentration of 0.00667% (Merck Frosst, Quebec, Canada).…”
Section: Regulation Of Cox-2 Expression In Vitromentioning
confidence: 99%
“…Accordingly, a variety of pharmacological agents known as non-steroidal antiin¯ammatory drugs (NSAIDs) can e ciently block cyclooxygenase activity and have bene®cial properties in colorectal cancer prevention. Recently, speci®c NSAIDs were developed that selectively block only COX-2, such as DFU (5,5-dimethyl-3-(3-¯uorophenyl)-4-(4-methylsulphonyl)phenyl-2(5H)-furon one) (Chan et al, 1997) and (Black et al, 1998). COX-2 is implicated as a factor in tumor initiation in colonic neoplasia due to mutations in the APC gene.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of COX-2 in the prolonged regulation of renal blood flow (RBF) and glomerular filtration rate (GFR) during changes in sodium intake is not well defined. [5][6][7][8] In the renal medulla, COX-2 expression increases in response to a high sodium intake. 3,4 Considering the role of prostaglandins (PGs) in the control of sodium excretion, 9 it may be proposed that COX-2 is more involved in regulating renal excretory function during high sodium intake than during normal sodium intake, but so far, it has not been evaluated whether this hypothesis is correct.…”
mentioning
confidence: 99%